2021
DOI: 10.1126/science.abi6087
|View full text |Cite
|
Sign up to set email alerts
|

Signaling inflammation across the gut-brain axis

Abstract: The brain and gastrointestinal tract are critical sensory organs responsible for detecting, relaying, integrating, and responding to signals derived from the internal and external environment. At the interface of this sensory function, immune cells in the intestines and brain consistently survey environmental factors, eliciting responses that inform on the physiological state of the body. Recent research reveals that cross-talk along the gut-brain axis regulates inflammatory nociception, inflammatory responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
234
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 398 publications
(240 citation statements)
references
References 65 publications
3
234
0
3
Order By: Relevance
“…For one, microaspiration during respiratory activity, such as oral breathing, affects the lung microbiota [ 7 ]. In addition, dietary patterns dynamically affect the microbiome profile of the GI tract either by microbial contamination or by supplying specific nutrients for microbial commensals, even manipulating the pathophysiology of cancerous diseases [ 8 , 9 ] as well as regulating immune responses across the gut–brain axis [ 10 , 11 ]. As such, along with the revolution of human microbiome research, much effort has been dedicated to figuring out the relationship between the oral and gut microbiota, which has been dubbed the “oral–gut–brain axis” [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For one, microaspiration during respiratory activity, such as oral breathing, affects the lung microbiota [ 7 ]. In addition, dietary patterns dynamically affect the microbiome profile of the GI tract either by microbial contamination or by supplying specific nutrients for microbial commensals, even manipulating the pathophysiology of cancerous diseases [ 8 , 9 ] as well as regulating immune responses across the gut–brain axis [ 10 , 11 ]. As such, along with the revolution of human microbiome research, much effort has been dedicated to figuring out the relationship between the oral and gut microbiota, which has been dubbed the “oral–gut–brain axis” [ 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that disorders of the intestines can aggravate the inflammation of the central nervous system ( Agirman et al, 2021 ). In our study, we discovered that the gavage of periodontitis salivary microbiota aggravated ischemic stroke and exacerbated inflammation in the ischemic brain.…”
Section: Discussionmentioning
confidence: 99%
“…While the responsible microbiotal products remain to identified in many cases, a voluminous literature documents the profound influence of the microbiota on host inflammatory responses in the gut, lung, brain, and skin ( Agirman et al., 2021 ; Blander et al., 2017 ; Chen et al., 2018 ; Rosshart et al., 2019 ).…”
Section: Inflammation-regulating Metabolitesmentioning
confidence: 99%